Investigating regulatory patterns of NLRP3 Inflammasome features and association with immune microenvironment in Crohn’s disease - Wu, Huihuan; Zeng, Ruijie; Qiu, Xinqi; Chen, Kequan; Zhuo, Zewei; Guo, Kehang; Xiang, Yawen; Yang, Qi; Jiang, Rui; Leung, Felix W.; Lian, Qizhou; Sha, Weihong; et al. (Frontiers in Immunology, 2023)
Crohn’s disease is characterized of dysregulated inflammatory and immune reactions. The role of the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome in Crohn’s disease remains largely unknown. Herein, we explored the role of NLRP3 inflammasome and its related genes in Crohn’s disease based on microarray-based transcriptomic data. The expressions of NLRP3 inflammasome-related genes were increased in diseased tissues, and higher expressions of NLRP3 inflammasome-related genes were correlated with generally enhanced immune cell infiltration, immune-related pathways, and human leukocyte antigen (HLA)-gene expressions. The gene-based signature showed well performance in the diagnosis of Crohn’s disease. Moreover, consensus clustering identified two Crohn’s disease clusters based on NLRP3 inflammasome-related genes, and cluster 2 was with higher expressions of the genes. Cluster 2 demonstrated upregulated activities of the immune environment in Crohn’s disease. Furthermore, four key hub genes were identified and potential drugs were explored for the treatment of Crohn’s disease. Our findings indicate that NLRP3 inflammasome and its related genes could regulate immune cells and responses, as well as involve in the pathogenesis of Crohn’s disease from transcriptomic aspects. These findings provide in silico insights into the diagnosis and treatment of Crohn’s disease, and might assist in the clinical decision-making process.